ANALISIS KESALAHAN BERBAHASA PADA KETERANGAN POSTINGAN INSTAGRAM (CAPTION) AKUN INSTAGRAM BERITA LAMONGAN PERIODE APRIL-JUNI - Eka Nur Aminatus Sholihah; Sisilia Tri Utami; Dinda Dwi Elisanti; Jazilatul Khoiro; Faishol Lutfillah Albart; Laila Tri Lestari; Bisarul Ihsan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and describe the types of language errors found in the captions of the “Berita Lamongan” Instagram account during the period of April–May 2026. A descriptive-qualitative method was employed, utilizing data collection techniques such as documentation, observation, and note-taking. The data sources consisted of linguistic units specifically words, phrases, and sentences containing deviations from Indonesian language rules. The results indicate that the language errors encompass aspects of spelling, word choice (diction), sentence structure, punctuation, capitalization, and the phenomenon of code-mixing. Key factors contributing to these errors include the dominance of informal language styles typical of social media and a lack of editing prior to publication. This study is expected to provide constructive input for media administrators to improve the quality of Indonesian language usage in the digital realm, particularly on newsoriented social media platforms.